JALAN LAIN POLITIK PROFETIK; SEJARAH SEBAGAI MOMEN ESKATOLOGIS - Asri, Syamsul (JPP (Jurnal Politik Profetik), 2013)
This article is aimed at delving into the very meaning of prophetic politics from various angles, and at the same time, criticizing the current labeling of ‘prophetic,’ which is mostly applied to legitimate and accelerate a double operation of certain pseudo socio-political interests. The word ‘prophetic’ should truly rely upon the conceptual nature of prophetus. First is to compare the history of philosophy to explain the position of propheticness within philosophical establishment which deals with the way to understand the history. Second is to explore the term of insan kamil as narative media to explain ‘human beings’ and the installation of ‘perfect human beings’.